Vitamin D status and its associations with bone mineral density, bone turnover markers, and parathyroid hormone in Chinese postmenopausal women with osteopenia and osteoporosis - Chen, Xi; Shen, Li; Gao, Chao; Weng, Rou; Fan, Yier; Xu, Shuqin; Zhang, Zhenlin; Hu, Weiwei (Frontiers in Nutrition, 2024)
Background: Vitamin D is a key factor in bone metabolism, yet vitamin D insufficiency and deficiency are prevalent among postmenopausal women, with potential repercussions on bone mineral density (BMD), bone turnover markers (BTMs), and parathyroid hormone (PTH). Nonetheless, the findings from existing studies exhibit inconsistency, and a notable gap exists in the availability of large-scale investigations. Methods: In this real-world study, 8532 postmenopausal women over 50 years old with a diagnosis of osteopenia (50.9%) and osteoporosis (49.1%) at the first visit were enrolled in this study. Serum 25(OH)D level, PTH and two BTMs: osteocalcin (OC) and Beta-CrossLaps of type 1 collagen containing cross-linked C-telopeptide (β-CTX), were measured. BMD at all sites were obtained by dual-energy X-ray absorptiometry (DXA). The associations of serum 25(OH)D level with BMDs and BTMs were investigated using spearman correlation analysis and analysis of general linear model adjusted by age and body mass index. Results: The serum 25(OH)D level was 22.17±9.75ng/mL among all patients included in this study. For the osteopenia group, the serum 25(OH)D level was 22.40±9.41 ng/mL, while for the osteoporosis group, it measured 21.93±10.08 ng/mL. In the osteopenia group, the prevalence of vitamin D deficiency, insufficiency and sufficiency was 45.8%, 34.6% and 19.6%, respectively, which was close to that of the osteoporosis group (47.4%, 34.3% and 18.3%) (P=0.202). Spearman correlation analysis unveiled negative associations between serum 25(OH)D concentrations and both BTMs and PTH. In the osteoporosis group, there were positive correlations between 25(OH)D levels and femoral neck BMD (r=0.040, P=0.010) and total hip BMD (r=0.053, P=0.001). Furthermore, we found that for the osteopenia group, vitamin D levels were associated with femoral neck BMD(P=0.020) and total hip BMD(P=0.008) and β-CTX (P<0.001), OC(P<0.001), and PTH(P<0.001). The same trends were seen in osteoporosis patients (P<0.05), and with greater lumbar spine BMD with increasing levels of 25(OH)D (P=0.009). Conclusion: This study showed high prevalence of vitamin D deficiency and insufficiency in Chinese postmenopausal women with osteopenia and osteoporosis and the relationships between vitamin D and BMD, BTMs and PTH. The results contribute to a more comprehensive understanding of how vitamin D may impact bone health.